Association of Aging with Fungal Nail Infections Among Diabetic and Non-Diabetic Population (Journal of Rashid Latif Medical College, 2025)
Background: Onychomycosis is a common chronic fungal infection of the nail plate caused by dermatophytes, yeasts, and molds. Advancing age and diabetes mellitus are well-recognized risk factors that predispose people to onychomycosis because of impaired circulation and immunity.Objective: To compare the prevalence and characteristics of fungal nail infections in diabetic and non-diabetic patients, and further to assess the influence of aging on the rates of infection.Methodology: A comparative cross-sectional study was carried out from January to July 2025 in the Departments of Medicine and Dermatology, Sir Ganga Ram Hospital, Lahore, and included a total of 200 patients aged 30 years and above presenting with discolored, brittle, or thickened nails. Of these, 100 were diabetics (Group A) and 100 were non-diabetics (Group B). Nail clippings were collected and examined microscopically by KOH preparation, then cultured on Sabouraud dextrose agar. SPSS version 25 was used for analyzing demographic and clinical data, and chi-square test was applied for comparison.Results: Fungal infection was found in 68% of diabetic patients and 40% in the nondiabetic group; p<0.001. In both groups, the infection rate increases with age and reaches 80% in diabetics above 60 years of age. Trichophyton rubrum was the most prevalent isolate encountered (61%), followed by Candida albicans (22%).Conclusion: Fungal infection of nails is highly prevalent among diabetics and increases with age. Regular examination of nails, good control of blood sugar levels, and early commencement of antifungal treatment will help in reducing morbidity among diabetics and the elderly population.